The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s13028-018-0358-8
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of insulin responses to standard dosed oral glucose tests (OGTs) via naso-gastric tubing towards definition of an objective cut-off value

Abstract: BackgroundInsulin dysregulation (ID) with basal or postprandial hyperinsulinemia is one of the key findings in horses and ponies suffering from the equine metabolic syndrome (EMS). Assessment of ID can easily be performed in clinical settings by the use of oral glucose challenge tests. Oral glucose test (OGT) performed with 1 g/kg bodyweight (BW) glucose administered via naso-gastric tube allows the exact administration of a defined glucose dosage in a short time. However, reliable cut-off values have not been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 22 publications
(28 reference statements)
0
17
0
Order By: Relevance
“…As an alternative, the OGT can be performed with 1.0 g/kg BM glucose dissolved in 2 L of water and administered via nasogastric tube as long as sedation or stressful restraint are not required . The suggested cutoff value for this test protocol is 110 μIU/mL insulin at 120 minutes, using the equine optimized insulin ELISA …”
Section: Laboratory Diagnosismentioning
confidence: 99%
“…As an alternative, the OGT can be performed with 1.0 g/kg BM glucose dissolved in 2 L of water and administered via nasogastric tube as long as sedation or stressful restraint are not required . The suggested cutoff value for this test protocol is 110 μIU/mL insulin at 120 minutes, using the equine optimized insulin ELISA …”
Section: Laboratory Diagnosismentioning
confidence: 99%
“…The AUCinsulin OGT differed, whereas the AUCglucose OGT did not differ between HR and LR animals, suggesting that HR horses secrete more insulin to maintain their glucose homeostasis after the oral glucose challenge. According to recently published reference ranges for OGT procedures performed by nasogastric intubation and quantification of equine insulin with the ELISA used in the present study, insulin concentrations above 110 µIU/mL insulin at 120 minutes are indicative for ID (Warnken et al 2018). If this cut-off is supplied to the oral sugar test (OGT) data only one horse (horse 10) has slightly elevated insulin response in OGT with 114 µIU/mL.…”
Section: Variations In Dynamic Insulin Responses and Plasma Insulin Cmentioning
confidence: 83%
“…If this cut-off is supplied to the oral sugar test (OGT) data only one horse (horse 10) has slightly elevated insulin response in OGT with 114 µIU/mL. It has been reported that insulin responses after OGT show wide variation and fluent transition from IS to ID (Warnken et al 2018). However, it remains unclear whether these clear differences between horses were normal physiological variation or already indicative of subclinical abnormalities which may predispose these four individuals to develop metabolic pathologies.…”
Section: Variations In Dynamic Insulin Responses and Plasma Insulin Cmentioning
confidence: 99%
“…Current Irish guidelines for the use of antivirals recommend antivirals for the treatment of uncomplicated influenza in at-risk groups i.e. those ≥65 years of age, pregnant women, residential care facilities residents, immunosuppressed individuals, individuals with chronic medical conditions and for treatment of clinically complicated influenza [ 14 ]. Targeted use of antivirals for post-exposure prophylaxis is also recommended for those in these at-risk groups.…”
Section: Discussionmentioning
confidence: 99%